"Communication and Leadership "Mahatma Gandhi as a Great Leader - Hassoon, Adeeb Obaid (Journal of Economic, Administrative and Legal Sciences, 2018)
In this article the author explored communication and Leadership qualities of Mahatma Gandhi. Based on the literature review, the author started with a brief history of Mohandas Gandhi, then how Mahatma Gandhi used effective communication as a leader to create effect impact on the people as well as other leaders in India and aboard.Mahatma Gandhi personified the Servant Leadership Behavior. He was broadly perceived as one of the twentieth century's most prominent political and profound pioneers. Regarded in India as the dad of the country, he spearheaded principle of Satyagraha—resistance to tyranny through mass peaceful common rebellion.More than whatever else his request for truth was, the real administration quality which he attempted to soak up in his supporters and second rank pioneers alike. Gandhi all through his profession trusted that he is not an additional conventional person and he resembles his other individual compatriots. He trusted that in the event that he has turned into an honorable identity then he has progressed toward becoming it since he pursued a few standards honestly, and any individual who can tail it can turn into a respectable and holy person like-individual as was he. The dialect, the style of Gandhi and his utilization of the verbal and non-verbal assets for informative purposes anticipate watchful examination. To comprehend his viability as a communicator one may likewise think about concentrates his thoughts and musings.
Keywords: Leadership; Leader; Satyagraha; Mahatma Gandhi